2013
DOI: 10.1098/rsif.2012.0587
|View full text |Cite
|
Sign up to set email alerts
|

Macroscale adhesion of gecko setae reflects nanoscale differences in subsurface composition

Abstract: Surface energies are commonly used to determine the adhesion forces between materials. However, the component of surface energy derived from long-range forces, such as van der Waals forces, depends on the material's structure below the outermost atomic layers. Previous theoretical results and indirect experimental evidence suggest that the van der Waals energies of subsurface layers will influence interfacial adhesion forces. We discovered that nanometre-scale differences in the oxide layer thickness of silico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
54
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 51 publications
2
54
0
1
Order By: Relevance
“…These model substrates have shown to be well suited to probe the influence of vdW interactions in biological systems, since their surface characteristics are identical within the experimental error while their subsurface contribution is different. 33,[37][38][39] As shown in Fig. 4, adhesion force measurements with the same cells (N = 25 cells) on both types of substrates are in excellent agreement.…”
Section: Van Der-waals Interactionssupporting
confidence: 60%
“…These model substrates have shown to be well suited to probe the influence of vdW interactions in biological systems, since their surface characteristics are identical within the experimental error while their subsurface contribution is different. 33,[37][38][39] As shown in Fig. 4, adhesion force measurements with the same cells (N = 25 cells) on both types of substrates are in excellent agreement.…”
Section: Van Der-waals Interactionssupporting
confidence: 60%
“…45 Moreover, adhesion experiments with setal arrays of live geckos revealed that the adhesion force was significantly varied by a change in the substrates subsurface composition. 46 …”
Section: Interactions In Biological Systemsmentioning
confidence: 99%
“…Silane layers in particular are mechanically robust, thermally stable up to at least 250 ∘ C and are not subject to swelling in the presence of solvents. These properties render silane‐coated substrates ideal model surfaces to study a wide range of physical, chemical and biological phenomena such as adhesion, adsorption, friction or nanofluidics of thin liquid films . Technical applications also benefit from the unique properties of SAMs: They act, for example as lubrication layers in micro‐electro‐mechanical systems or as coatings in microfluidic devices .…”
Section: Introductionmentioning
confidence: 99%